Sports Participation Correlates With Academic Achievement: Results From a Large Adolescent Sample Within the 2017 U.S. National Youth Risk Behavior Survey. Issue 2 (April 2020) - Burns, Ryan D.; Brusseau, Timothy A.; Pfledderer, Christopher D.; Fu, You
This study sought to examine associations between (a) sports team participation; (b) lifestyle behaviors (e.g., sleeping, alcohol, and tobacco use); and (c) dietary behaviors with self-reported academic achievement using data derived from the 2017 U.S. National Youth Risk Behavior Survey. A multistage cluster sampling procedure was employed to obtain a representative sample of U.S. adolescents from among whom the number with usable data was 14, 765. We used weighted logistic regression models to examine the associations between sports participation, lifestyle behaviors, and diet with reported academic achievement (mostly A's and B's), adjusting for age, sex, body mass index, and race/ethnicity. After controlling for lifestyle behaviors, diet, and other potentially confounding variables, we found that adolescents participating in one or more sport teams throughout the past year also reported higher academic achievement (A's and B's) compared with adolescents participating in zero sports teams (odds ratio [ OR ] = 1.39 to 2.40, p < .001). This relationship was dose-dependent, as participating in multiple sports teams (i.e., > 3) showed a stronger association with academic achievement than participating on only one sports team ( p < .001). Other independent behavioral correlates with similarly high grades included daily breakfast consumption ( OR = 1.40, p < .001), sleeping at least eight hours per night ( OR = 1.21, p < .001), and regular consumption of vegetables ( OR = 1.56, p < .001) and salads ( OR = 1.30, p < .001). We discuss the meaning and implication of these findings.